Relationship between stair-climbing rate, balance and motor recovery in individuals with hemiparesis - Amaral-Natalio, Mavie; Nunes, Guilherme da Silva; Herber, Vanessa; Michaelsen, Stella Maris (Acta Fisiátrica, 2011)
Objective: To study the relationship between the cadence when climbing up and down stairs, and the levels of motor recovery of the lower limbs and dynamic balance of individuals with hemiparesis. Method: The study included 16 individuals with hemiparesis due to stroke, of which 13 were men with a mean age 56.6±12.6 years. The stair-climbing cadence was measured by elapsed time (steps/minute), separately, for climbing up and down four steps (height: 17 cm) at a comfortable speed.  Results: The average cadence when climbing up the stairs was 60.4±22.6 steps/ minute and when climbing down was 58.7±23.6 steps/minute. The level of motor recovery of the lower limbs was 24.8±5.2 points on the Fugl-Meyer Scale, and the TUG average was 19.8±23.1 seconds. Moderate correlation was found between the measurement of the cadence when climbing up the stairs and the levels of motor recovery (r= 0.60, p= 0.01) and dynamic balance (r= -0.61, p= 0.01). Likewise, the measurement of the cadence when climbing down the stairs presented a moderate correlation with the level of motor recovery (r= 0.58, p= 0.02), and with the degree of dynamic balance (r= -0.64, p= 0.007).  Conclusions: The ability to climb up and down stairs is correlated to motor recovery of the lower limbs, and the dynamic balance is more closely correlated to the cadence of climbing down stairs in individuals with hemiparesis.